Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1055/s-0034-1393183
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided needle-based confocal laser endomicroscopy for diagnosis of solid pancreatic lesions (ENES): a pilot study

Abstract: Background and study aims: Endoscopic ultrasound-guided needle-based confocal laser endomicroscopy (EUS-nCLE) has been shown to aid in the diagnosis of cystic pancreatic lesions. This is a pilot project to study its findings in patients with solid pancreatic lesions (SPLs) with a prospective single-blinded study design. Methods: Patients with SPLs undergoing trans-gastric EUS fine needle aspiration (EUS-FNA) from July 2013 to March 2014 were prospectively enrolled. The nCLE diagnoses were compared with the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Furthermore, these results persisted in Asian patients diagnosed in late stages: a higher overall survival (3.3 months) was recorded versus Caucasians (2.9 months) or African Americans and Hispanics (2.6 months for both subgroups) [37]. A study conducted in Thailand also confirmed that outcomes in Asians and Caucasians with pancreatic cancer are similar, although the overall survival is lower (5.1 months) [38]. Isherwood et al reported that Asians/Asian British had higher overall survival and survival for subjects who received palliative therapy (6.1 months and 5.1 months, respectively) compared to White British (4.6 months and 3.7 months, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, these results persisted in Asian patients diagnosed in late stages: a higher overall survival (3.3 months) was recorded versus Caucasians (2.9 months) or African Americans and Hispanics (2.6 months for both subgroups) [37]. A study conducted in Thailand also confirmed that outcomes in Asians and Caucasians with pancreatic cancer are similar, although the overall survival is lower (5.1 months) [38]. Isherwood et al reported that Asians/Asian British had higher overall survival and survival for subjects who received palliative therapy (6.1 months and 5.1 months, respectively) compared to White British (4.6 months and 3.7 months, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…A pilot study of nCLE for diagnosis of pancreatic mass lesions has reported findings of dark clumps measuring greater than 40 µm associated with malignancy, no complications, and good interobserver agreement amongst three endosonographers blinded to all clinincal data. However, this technology will require further evaluation to determine its place in diagnosis of solid pancreatic masses[ 100 ].…”
Section: Other Tools On the Horizonmentioning
confidence: 99%
“…Although the current studies on nCLE diagnoses of pancreatic solid lesions are limited, they have all shown a high accuracy rate. In the study by Kongkam et al .,[ 22 ] 22 patients were recruited, and EUS-nCLE yielded satisfactory images in all patients during the first EUS procedure. The study yielded diagnoses of benign and malignant solid pancreatic lesions (SPLs) in 3 and 19 patients, respectively.…”
Section: Needle-based Confocal Laser Endomicroscopy In Solid Pancreatmentioning
confidence: 99%